Analisis In Silico Senyawa Curcuma xanthorrhiza dan Moringa oleifera sebagai Kandidat Antiinflamasi - Syamsi, Lusi Nursilawati; Syamsudin, Syamsudin; Mumpuni, Esti; Widowati, Wahyu; Nursanti, Okta; Qodriah, Rahmatul (State University of Gorontalo, 2025)
Inflammation is the body's immune response to pathogens, tissue injury, or exposure to toxic substances. The search for effective anti-inflammatory agents remains a key focus in pharmaceutical and healthcare research. Temulawak (Curcuma xanthorrhiza) and Moringa (Moringa oleifera) have been widely used in traditional medicine due to their bioactive compounds with potential anti-inflammatory effects. This study aims to evaluate the molecular interactions between curcumin from temulawak, as well as quercetin and kaempferol from moringa, against inflammatory targets using an in silico approach through molecular docking and molecular dynamics simulations.